Agro-Technical Basis for Spring Rape Seed Productivity Depending on Different Climatic Zones of the Russian Federation - Nurlygaianov, Razit; Ismagilov, Rafael; Islamgulov, Damir; Ahiyarov, Bulat; Abdulvaleev, Rishat; Ismagilov, Kamil; Ginijtova, Fanzilja (International Journal of Advanced Science and Technology, 2019)
The article deals with the features of spring rape mineral nutrition. The planned yield level of spring rape seeds is not formed under production conditions, the actual value is lower than planned one. A higher dose of mineral fertilizer, application types and methods increased the growing season for 19 days. The yield varied from 1,3 t/ha to 2,2 t/ha, oil content varied from 43,0 to 46,0%. Spring rape seed harvesting is the main stage in the cultivation technology. The yield and seed fat content depend on harvest time and methods. In single-stage harvesting the loss of spring rape seeds is higher as compared to control by 3 %, but the loss is less by 4,0 % than in two-stage harvesting. The treatment of crops with the Basta VR desiccant allows us to reduce the yield losses of spring rape seeds by 1,1 % compared to direct combining and by 4.9 % compared to two-stage harvesting. At the humidity of 15 % and below, the full seed formation with an oil content of 38,6% is completed. The oil yield from 1 hectare is 0,56 t/ha. It is necessary to develop adaptive technologies taking into account soil-climatic conditions and biological crop potential in all climatic zones of the Russian Federation where there is a possibility of cultivation of spring rape for seeds.